Orchard systems offer low-hanging fruit for low-carbon, biodiversity-friendly farming - Wyckhuys, Kris A.G.; Abram, Paul K; Barrios, Edmundo; Cancino, Jorge; Collatz, Jana; Fancelli, Marilene; Klein, Alexandra-Maria; Lindell, Catherine A.; Osterman, Julia; Pinto, Maria; Tang, Fiona H.M.; Tena, Alejandro; et al. (Oxford, 2025)
As core constituents of healthy diets, fruits are often cultivated in temporally stable and structurally complex ecosystems that harbor high levels of biodiversity. However, high-intensity orchard management can lessen the human and environmental health benefits of fruticulture. In the present article, we argue that increased emphasis on biological control could contribute to preventative manage- ment of fruit pests, weeds, and diseases, resulting in pesticide phasedown. Carefully calibrated orchard management can increase the provision of ecosystem services by above- and belowground biota, improve soil health, and store atmospheric carbon. When tactically integrated with agroecological measures, behavior-modifying chemicals, or digital tools, biological control helps to conserve pollinator or soil fauna, protect vertebrate communities, and improve vegetation restoration outcomes. Its implementation can, however, give rise to scientific and social challenges that will need to be explored. By resolving the adoption hurdles for biological control at scale, human society could enjoy the myriad benefits of nature-friendly fruit production